ANALISIS PENANAMAN KARAKTER RELIGIUS PADA PESERTA DIDIK KELAS V DI SDN SINDANGSARI - Hamidah, Wanda; Anjaswuri, Fitri; Muhajang, Tatang; A. Gani, Resyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students need to have a religious character as this helps to develop noble values and a strong understanding of religion, which are essential for success in sustainable living. Cultivating religious character needs to start from elementary school, including in grade V students of SDN Sindangsari. Unfortunately, the study of religious character cultivation in students has not been observed, therefore, the encouragement to research the analysis of religious character cultivation in grade V students at SDN Sindangsari is in-depth. The purpose of this study is to analyze the cultivation of religious character in class V students at SDN Sindangsari. This study uses a qualitative descriptive approach with a strategy of collecting data from interviews, observations, recordings, and distributing questionnaires. Student participants and teachers of grade V of SDN Sindsngsari. Extensive analysis will be carried out using the research data obtained. The findings of the study show that when teachers exemplify good religious character, through YouTube videos by acting out characterizations involving their students, it has a great positive impact on their students, including teaching five prayers at five times, teaching strategies for reading the Qur'an, and equipping students with the values of cultivating religious character. Teachers must also ensure that their students can worship and show obedience to their religious teachings, such as praying before and after studying. Positive traits that teachers must have include not discriminating against religious beliefs always being actively involved in every learning and always respecting and obeying religious regulations. This is continuously carried out in every learning in the classroom and applied in the personal lives of students.